Notes d'Allemagne (1923) - Serge, Victor; Lvovitsj Kibaltsjitsj, Viktor; Broué, Pierre (Montreuil : La Brèche-PEC, 1990)
Bibliotheek François Vercammen
Frans
Monografie
Keywords: Derde Internationale (1919-1943).; politieke geschiedenis; Duitsland